2013
DOI: 10.1177/1933719112459241
|View full text |Cite
|
Sign up to set email alerts
|

A Phytooxysterol, 28-Homobrassinolide Modulates Rat Testicular Steroidogenesis in Normal and Diabetic Rats

Abstract: Steroidogenesis in testicular cells depends upon the availability of cholesterol within testicular mitochondria besides the activities of 3b-hydroxysteroid dehydrogenase (3b-HSD, 17b-hydroxysteroid dehydrogenase [17b-HSD]), and the tissue levels of steroidogenic acute regulatory protein (StAR), androgen-binding protein (ABP), and testosterone (T). Cellular cholesterol biosynthesis is regulated by endogenous oxycholesterols acting through nuclear hormone receptors. Plant oxysterols, such as 28-homobrassinolide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The observed sever decreases in testosterone level and steroidogenic enzyme activity in the diabetic animal considered as a consequent destruction of gonadic function due to hyperglycemia [14,15]. 28-HC greatly augmented rat testicular and plasma testosterone level both in treated normal and diabetic rats even though diabetic rat testicular testosterone level was greatly attenuated conforming that this brassinosteroid keto isoform functioned verse similar to the hydroxy form 28-HB in inducing testicular testosterone levels as reported by Premalatha et al [16].…”
Section: Discussionsupporting
confidence: 65%
“…The observed sever decreases in testosterone level and steroidogenic enzyme activity in the diabetic animal considered as a consequent destruction of gonadic function due to hyperglycemia [14,15]. 28-HC greatly augmented rat testicular and plasma testosterone level both in treated normal and diabetic rats even though diabetic rat testicular testosterone level was greatly attenuated conforming that this brassinosteroid keto isoform functioned verse similar to the hydroxy form 28-HB in inducing testicular testosterone levels as reported by Premalatha et al [16].…”
Section: Discussionsupporting
confidence: 65%
“…The present study was designed to elucidate the effects of olive extract on testicular steroidogenesis in STZ-induced diabetic rats. Accumulating evidences have verified that dysfunction of testicular steroidogenesis and spermatogenesis resulted from hyperglycaemia-induced oxidative stress and insulin deficiency is associated with male reproductive impairment (Premalatha et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has confirmed that testicular steroidogenesis and spermatogenesis dysfunction correlate with male reproductive failure, due to hyperglycemic oxidative stress and insulin deficiency [ 84 ]. Testicular steroidogenesis is a highly regulated cholesterol-controlled signaling pathway that is dependent on cholesterol that is accessible within testicular mitochondria controlled by StAR [ 85 ].…”
Section: Discussionmentioning
confidence: 99%